Konsep Menyerahkan Orang Kepada Iblis dalam 1 Korintus 5:1-13 dan Implementasinya dalam Kehidupan Orang Percaya - Malau, Andre; Luthy, Christopher James; Laukapitang, Yunus D. S. (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
The basic diificulty in understanding the text is understanding the role of the devil who destroys the body but aims to save the soul of the person who is handed over to the devil which is very contrary to the goal of the devil who wants to destroy humans so that they experience eternal death instead of saving the soul. The purpose of this study is to examine the concept of handing people over to the devil in the text of 1 Corinthians 5:1-13. In addition, the author also explains the implications of the text for believers today. This study uses a grammatical-historical hermeneutic study method. The result of the author's study is that the concept of handing people over to the Devil in 1 Corinthians 5:1-13 is an act of the congregation by exercising church discipline against church members who have not left their sins and aims to provide a deterrent effect. Meanwhile, the implementation of the concept of handing people over to the Devil/demons in 1 Corinthians 5:1-13 is that believers live in a commitment to holiness, carry out church discipline as the identity of the holy people, and carry out church discipline as the authority of the congregation. Kesulitan dasar dalam memahami teks tersebut ialah memahami peran Iblis yang membinasakan tubuh namun bertujuan untuk keselamatan roh atas orang yang diserahkan kepada Iblis yang sangat bertentangan dengan tujuan Iblis yang mau membinasakan manusia agar mengalami kematian kekal bukan keselamatan roh. Tujuan dari penelitian ini ialah mengkaji konsep menyerahkan orang kepada Iblis dalam teks 1 Korintus 5:1-13. Selain itu, penulis juga menjelaskan implikasi teks bagi orang percaya pada masa kini. Penelitian ini menggunakan metode kajian hermeneutik gramatikal-historis. Hasil kajian penulis ialah konsep menyerahkan orang kepada Iblis dalam 1 Korintus 5:1-13 adalah tindakan jemaat dengan menjalankan disiplin gereja terhadap anggota jemaat yang belum meninggalkan dosanya dan bertujuan memberikan efek jera. Adapun, implikasi dari konsep menyerahkan orang kepada Iblis/setan dalam 1 Korintus 5:1-13 ialah orang percaya hidup dalam komitmen kekudusan, menjalankan disiplin gereja sebagai identitas umat yang kudus, serta menjalankan disiplin gereja sebagai wewenang jemaat.